PENYELENGGARAAN PEMERINTAHAN NAGARI: ANTARA FORMAT ADAT ATAU FORMAT NEGARA - Afwadi Dt (Institut Agama Islam Negeri Batusangkar, 2017)
Kembali ke Nagari and Kembali ke Sistem Pemerintahan Nagari (literally means Back to the Nagari and Back to the governmental system of Nagari) are genuine needs of local society of Minang Kabau in West Sumatera Province. However, the implementation is not as easy as it sounds. Various problems might be encountered, such as ambiguity and dualism dealing with governmental concept whether local (adat) format or national one. This paper basically deals with the debate both in term of concept and reality upon the reimplementation of the governmental system of Nagari. On one hand, nagari is the smallest form of national governmental system. On the other hand, sociohistorically, nagari is a ‘mini’ republic which is governed by the rules of adat. Therefore, an integrative combination for the format of governmental system of Nagari should be carefully formulated.